Cover Image. (14th February 2023) - Steffensen, Ellen Hollands; Skakkebæk, Anne; Gadsbøll, Kasper; Petersen, Olav Bjørn; Westover, Thomas; Strange, Heather; ,; Vogel, Ida
Abstract : The cover image is based on the Original Article Inclusion of sex chromosomes in noninvasive prenatal testing in Asia, Australia, Europe and the USA: A survey study by Ellen Hollands Steffensen et al., https://doi.org/10.1002/pd.6322 . Image Credit: Ellen Hollands Steffensen. Created with mapchart.net.